'What was required above all else was collaboration': keeping the momentum for SEND partnership working in the wake of Covid‐19. (10th May 2022) - Hellawell, Beate; Smith, Sharon; Wharton, Julie
Abstract : This article considers implications for partnership working across the Special Educational Needs and Disabilities (SEND) system in England, at a time when a long‐overdue SEND Review is imminent and the SEND Code of Practice 2015 is awaiting a significant overhaul. It highlights the role local policy actors occupy within this system, as the progression of the Covid‐19 pandemic moves SEND partnerships towards a 'new normal' and there is heightened concern about missed opportunities for reform and renewal. Previously published findings from an online questionnaire (n = 100) undertaken by the Special Educational Needs Policy Research Forum provided insight into how school staff had been supported in the teaching of pupils with SEND during periods of school closures and what lessons had been learned. The present article offers a thematic analysis of the narrative responses provided in addition to the closed survey questions. The analysis generated six statements that can be understood as lessons learned from the pandemic for partnership working, drawing on the experiences of parents, school staff, and advising professionals working in local authorities.